Organic Manures Integrated with Cover Crops Affect Both Cover Crop and Commercial Crop Performance Including Soil Health: Effect on Cover Crop Growth, Nitrogen Uptake, and Soil Mineral N - Paul Cottney; Lisa Black; Ethel White; Paul N. Williams (Agriculture)
Cover crops have many simultaneous roles that enhance the sustainability of agriculture compared to leaving land fallow in arable systems. In high rainfall climates, an important role of cover crops is to sequester nutrients, protecting them from loss to the environment. In many livestock intensive regions, organic manures are applied in autumn with land left fallow over winter and then a cash crop is planted in the spring. This practice of extended fallow, combined with the poorly synchronised application of nutrients to cash crop nutrient demand, further adds to the potential for large losses of nutrients specifically nitrogen (N) to the environment through leaching and volatilization. Therefore, if cover crops could respond to these nutrients through increased biomass growth and nutrient uptake, they could reduce these losses. Therefore, it is important to choose the correct species which grows adequately to deliver these potential benefits. In the region this study is conducted, Northern Ireland, there has been little research to investigate not only what optimum cover crop species are but also what species could respond to additional nutrients in the slurry. This study comprises two experiments, in consecutive years, including a combination of three factors: cover crop species (five species; a mixture and a control representing fallow); pig slurry. Consequently, it was found that with good growing conditions, in the trial year of 2018/19, species such as forage rape and tillage radish could significantly (p < 0.05) increase the amount of N contained in their biomass and the soil (to 15 cm) by 70 and 63%, respectively, in response to slurry. Alternatively, when slurry was applied to fallow land (conventional practice), low amounts (14 and 0% in the two trial years, respectively) of the N from the slurry were detected in weed biomass or retained in the soil. This demonstrates a large loss of N from the system. Thus, the integration of responsive cover crops with slurry is a better practice to abate N loss than conventional practice, if slurry applications can not be delayed.